Women's Micro Business Performance in Islamic Perspective: Social Learning Theory Approach - Fatimah, Salsabila Husnul; Nurasyiah, Aas; Rosida, Rida (Signifikan: Jurnal Ilmu Ekonomi, 2025)
Research Originality: This research examines the gender gap in the economic sector, particularly women's micro-enterprises in Indonesia, which has not been widely explored. With an Islamic approach and Albert Bandura's Social Learning Theory.Research Objectives: This study aims to describe the performance of women micro-entrepreneurs from an Islamic perspective and empirically prove the influence of competence, Islamic work ethic, family support, and manager role actualization on women's micro-enterprises in Bandung City.Research Methods: This study used a quantitative method with a descriptive causality research design. The survey method collected data from 236 female micro-business owners in Bandung City. The data was processed using the Partial Least Square—Structural Equation Modeling (PLS-SEM) analysis technique. Empirical Results: The results show that, from an Islamic perspective, competence and an Islamic work ethic positively affect women's micro-enterprise performance. However, family support has a negative influence on business performance.Implications: This research makes an important contribution to understanding the dynamics of women's micro-enterprise performance from an Islamic perspective. The results can be used as a basis for developing more effective programs and policies to support women's economic empowerment through micro-enterprises.JEL Classification: L26, J16, M10, M13, O17, Z12How to Cite:Fatimah, S. H., Nurasyiah, A., & Rosida, R. (2025). Women’s Micro Business Performance in Islamic Perspective: Social Learning Theory Approach. Signifikan: Jurnal Ilmu Ekonomi, 14(1), 217-230. https://doi.org/10.15408/sjie.v14i1.44739.